The sheik a novel - Hull, Edith M. (Pine Street Books, 2001)
Dana Mayo is young, beautiful, wealthy, and independent. Bored by the eligible bachelors and endless parties of the English aristocrats, she arranged for a trek through the Algerian desert. Two days into the her adventure, she is kidnapped by the powerful Sheik Ahmed Ben-Hassan, who forces her into submission. Dan tries desparately to resist but finds herself falling in love with the dark and handsome stranger. What follows is a tale of mystery, power, and forbidden love fulfilled.